Bordeline Cultural Practices in Modern Society: the Anthropo-Creating Function - Ludmila K. Nefedova; Amina Sh. Rudi; Olga M. Kordas (Журнал Фронтирных Исследований, 2023)
The purpose of this article is to examine borderline cultural practices that aid in the development of a modern person. We focus on the practices of consumption and childhood, which take shape at the frontier of global and local cultures, to explore their anthropo-creating function. We have identified two groups of cultural practices: socializing and individualizing, and we have synthesized subjective characteristics of cultural practices that best fulfill the function of creating a person. The article also presents a mechanism for developing consumer behavioral strategies that are not determined solely by the logic of the historical process of the existence of local cultures. It highlights the inclusive potential of global culture, which recognizes significant differences among peoples in their ideas about the world, value systems, and diverse trends and outcomes of historical development. Parenting practices also implement the principle of inclusiveness.